Recent developments in monetary theory and policy (with special reference to developing economics) : papers and proceedings of the seminar held at Bombay on January 14 and 15, 1978 - Reserve Bank of India (Bombay : Reserve Bank of India, Economic Dept., 1978)
The book highlighted some of the major issues in the field of monetary theory and policy. It stimulated an awareness of the problems and of the need for further theoretical and empirical analysis.
Includes bibliographical references
usc 09/11/17
Loans
Keywords: Monetary policy; Economic history; Money; Developing countries; India